Circulating tumor DNA for surveillance in high-risk melanoma patients: a study protocol - Magnús P.B. Obinah; Sarah A. Al-Halafi; Karin Dreisig; Tim S. Poulsen; Christoffer Johansen; Thomas Litman; Stig E. Bojesen; Estrid Høgdall; Annette H. Chakera; Lisbet R. Hölmich (Acta Oncologica)
Background and purpose: Melanoma is one of the deadliest skin cancers and challenges clinicians worldwide due to rising incidence, potential aggressiveness, and propensity for metastasis, necessitating comprehensive follow-up programs after primary treatment.